Khaana Khazana: Food Labor in Cosmopolitan India - Rastogi, Megha (The Columbia Journal of Asia, 2025)
This work aims to understand the relationship between food workers, gender norms, and class dynamics within economically and culturally diverse Indian cities. While food workers, specifically chefs and line cooks, inhabit a central role in urban food economies and cultural systems, their labor and positionality transcend the spatial confines of a restaurant. However, present research solely focuses on food workers as laborers, rather than considering how their positionality shapes local and regional sociopolitical processes. This gap has manifested in both the subjugation of food workers to the boundaries of the restaurant and a dearth of insight into their perspective regarding the experiences, principles, and values that govern their work. The physical space thus provides ethnographic glimpses of restaurants in India; the consumers and food workers present in a restaurant interact with the spatial boundaries of the eatery in significant ways. Interviews with the food laborers reveal wider implications about social values from their position in both local and global political economies. I contend that the experiences of food workers display characteristics of broader sociopolitical frameworks, where food workers contribute to the creation of sociopolitical cleavages within domestic and professional spaces. This research bridges these gaps through the triangulation of participant observation, qualitative interviews, and menu analysis at four eateries in Mumbai conducted over a week. I find that occupational limitations and systemic inequity of urban India faced by chefs have contributed to their views on gender, language, and westernization, thus impacting the larger political economy. The research suggests that Western ideals and influence shaped how some food workers in the Mumbai restaurant scene approached their work, while fiscal necessity motivated others. My study suggests important findings about the interplay between political economy and social factors—such as class, gender, and westernization—for food workers in major cities of the Global South. Through this project, I hope to highlight the agency of food workers: rather than viewing them through their occupation, this paper endeavors to view their occupation from the perspectives of food workers themselves.